How Have Green Companies Fared in Transactions with Banks? A Stakeholder‐Management Perspective. Issue 4 (14th February 2019) - Jin, Dawei; Liu, Liuling; Ma, Jun; Wang, Haizhi; Yin, Desheng
Abstract : In a recent study, the authors investigated whether and to what extent a company's environmental practices and record affect the terms of its bank loans. The study reports evidence of a clear association between environment‐friendly corporate practices and both lower borrowing costs and less use of restrictive financial covenants. And consistent with the above findings, the authors also report that companies with better environmental practices have more stable income streams, lower leverage ratios, and higher future valuations. The authors also find that relationship (as opposed to first‐time) lenders respond to improvements in companies' environmental records by offering more favorable borrowing terms over time. Moreover, the authors find that the association between more effective environmental management and lower loan costs is more pronounced for corporate borrowers that operate in industries facing greater industry competition and stricter environmental regulation. In addition, borrowers with better records for green management are less likely to violate covenants, default on loans, or file for bankruptcy—a conclusion that should shed light on the current green finance policy debate among central banks and regulators as to whether they should reduce capital requirements or offer other policy inducements for bank financing of green assets.